Systematic review of economic evaluations of aromatase inhibitors in estrogen receptor-positive breast cancer: quality evaluation - Maha F. Althuwaibi; Cristina Fernandez-Garcia; Louise Hayes; Richard McNally; Diarmuid Coughlan (BMC, 2023)
Abstract Background Breast cancer (BC) is a leading cause of premature death in women and the most expensive malignancy to treat. Since the introduction of targeted therapies has resulted in changes to BC therapy practices, health economic evaluations have become more important in this area. Taking generic medications, Aromatase Inhibitors (AIs), as a case study, we conducted a systematic review of the recent economic evaluations of AIs for estrogen receptor-positive breast cancer patients and evaluated the quality of these health economic studies. Objective To systematically review and examine the quality of the available economic studies of AIs in estrogen receptor-positive breast cancer. Methods A literature search was performed using six relevant databases (MEDLINE, Embase, Database of Abstracts of Reviews of Effects, Health Technology Assessment Database, NHS Economic Evaluation Database, and SCOPUS) from January 2010 to July 2021. All economic studies were independently assessed by two reviewers using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist to evaluate the quality of the economic evaluations. This systematic review is registered in the PROSPERO database. To compare the different currencies used in these studies, all costs were converted to international dollars (2021). Results A total of eight studies were included in the review; six (75%) were performed from the healthcare providers' perspective. They were conducted in seven different countries, and all were model-based analyses using Markov models. Six (75%) considered both Quality Adjusted Life Years (QALYs) and Life Years (LY) outcomes, and all costs were derived from national databases. When compared to tamoxifen, AIs were generally cost-effective in postmenopausal women. Only half of the studies addressed the increased mortality following adverse events, and none mentioned medication adherence. For the quality assessment, six studies fulfilled 85% of the CHEERS checklist requirements and are deemed good quality. Conclusion AIs are generally considered cost-effective compared to tamoxifen in estrogen receptor-positive breast cancer. The overall quality of the included studies was between high and average but characterizing heterogeneity, and distributional effects should be considered in any future economic evaluation studies of AIs. Studies should include adherence and adverse effects profiles to provide evidence to facilitate decision-making among policymakers.